What is the natural history of nonoperated nonfunctioning pituitary adenomas? - Karavitaki, N; Collison, K; Halliday, J; Byrne, J; Price, P; Cudlip, S; Wass, J (2007)
BACKGROUND: Series of patients systematically investigating the outcome of clinically nonfunctioning pituitary adenomas (NFAs) not treated by surgery or radiotherapy during long follow-up periods are limited. Most reports involve the follow-up of selected cases of incidentally found lesions, rendering their results unreliable on the assessment of the pros and cons of a 'watch and wait' policy. OBJECTIVE: To investigate the outcome of a series of consecutive patients with presumed NFA (microadenoma or macroadenoma), who were not offered treatment at presentation (for a number of reasons) and were regularly followed up, and to identify possible factors predicting subsequent increase in tumour size. PATIENTS AND METHODS: All patients presenting to the Department of Endocrinology in Oxford between 1989 and 2005 with presumed NFA were studied retrospectively. Inclusion criteria were: (i) imaging features suggestive of a pituitary adenoma, (ii) no clinical and/or biochemical evidence of hormonal hypersecretion by the tumour, (iii) monitoring being the initial choice of management, and (iv) at least one repeat scan during the follow-up period. Subjects presenting with acute apoplexy were excluded. Follow-up management included clinical evaluation, assessment of the visual acuity and fields and imaging at regular intervals. The duration of observation was estimated from the dates of first and last scan. RESULTS: Forty subjects were included in the study [18 males/22 females, median age 52 years (range 18-89), 16 with microadenoma/24 with macroadenoma]. The mean follow-up period was 42 months (range 8-128). During the observation interval, 12.5% of the microadenomas and 50% of the macroadenomas increased in size. The 48-month probability for enlargement was 19% for the microadenomas and 44% for the macroadenomas. Among the subjects with tumour enlargement, 57% showed new or worse visual field defects (all had macroadenomas) and 21% showed chiasmatic involvement on imaging without visual deterioration (all had macroadenomas). New or worse visual field defects were found in 67% of the macroadenomas showing increase in size. No microadenoma enlarged to cause visual deterioration. In microadenomas, sex and age at presentation were not predictors of enlargement. In macroadenomas, sex, age, visual field defects or cavernous sinus invasion at presentation were not predictors of enlargement. CONCLUSIONS: The 'watch and wait' policy seems reasonable for microadenomas but is probably not a safe approach for macroadenomas, which appear to have a significant growth potential; in these cases, given the lack of established medical treatment, the decision for surgical intervention should balance the presence of significant comorbidities and the anaesthetic/peri-operative risks at presentation against the probability of tumour enlargement and its consequences, as well as the possible loss of advantages associated with early operation.